Enxertia da pimenteira-do-reino em espécies nativas de Piper - Ferrari, Wesley Ribeiro (2021)
The black pepper crop in Brazil is affected by fusariosis, a disease caused by the fungus Fusarium solani f. sp. piperis, considered the main black pepper disease in the country, responsible for the reduction in productivity and longevity of crops, with no efficient management for the eradication of the disease. An important alternative that could allow the cultivation of black pepper in contaminated areas is the grafting on resistant wild species. However, the use of this technique is not yet established to produce seedlings, since there is a need to identify the graft compatibility in greater diversity of genotypes for rootstock and the best technique for that. Therefore, the aim of this study was to investigate the interaction between grafting methods and compatible rootstocks, aiming to determine the best combination, under nursery conditions, that would contribute to the establishment of a protocol to produce grafted seedlings. Black pepper grafting was evaluated using the techniques of side veneer grafting and wedge grafting in six different rootstocks, with four wild species (Piper aduncum Link, Piper tuberculatum Jacq., Piper marginatum Jacq. and Piper hispidum Kunth) and two cultivars of black pepper ('Kottanadan Broto Branco' and 'Bragantina'). The evaluations of setting, root development, aerial part and the quality parameters of the seedlings allowed to determine the initial compatibility of the black pepper grafting in Piper aduncum, by means of top grafting in full slit. The species Piper tuberculatum and Piper marginatum were shown to be incompatible for grafting with P. nigrum. The side veneer grafting method was not efficient to produce seedlings in the nursery conditions established for this experiment.